The Effect of Leadership and Organizational Commitment in Improving the Quality of Education at MPU Kuturan Singaraja - Julianingsih P, L. Eka M.; Yadnyawati, Ida Ayu Gde; Paramartha, Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate the impact of leadership and organizational commitment on improving the quality of education in rapidly growing educational institutions, enabling them to effectively compete with other universities. The approach used is a quantitative method, utilizing questionnaires as the primary means of data collection. The study encompassed a population of 2,335 individuals, with a sample size of 335. The research results show that: first, from the results of these calculations, it can be seen that sig. research < sig. 5%, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). This means that there is a significant influence of leadership on the quality of education at STAHN Mpu Kuturan Singaraja. Second, from the results of these calculations, it can be seen that the research sig is < sig 5%. The null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Therefore, these findings provide support for the research hypothesis, which posits a significant influence of organizational commitment on education quality at STAHN Mpu Kuturan Singaraja. Third, from the results of these calculations, it can be seen that the research sig is < sig 5%, leading to the rejection of the null hypothesis (H0).